Remittances, Institutions, and Economic Growth: The Case of the European Union - Trpeski, Predrag; Merdzan, Gunter (Eurasia Business and Economics Society, 2022)
Theoretical and empirical research on the impact of remittances on the economy has produced very different results. International remittances stimulate economic growth for many countries, mainly by increasing national disposable income. The paper empirically investigates the role of remittances and institutions in the economic growth of the 27 member states of the European Union (EU) from 1995-to 2019. The selected group of countries includes countries from different levels of economic development and countries from the former socialist system, countries that are in transition, countries that have successfully overcome that process, and traditionally capitalist countries with different quality of institutions. Using the generalized method of moments (GMM) in a data analysis panel, we found evidence that institutions play an essential role in how remittances affect economic growth. It has been found that a healthy institutional environment affects the volume and efficiency of investments; hence, in the presence of good institutions, remittances could be channeled more efficiently, which will eventually lead to greater output. The paper also proves that with better institutional quality in the country, the effect of remittances and other economic and financial activities is more pronounced. Thus, to the extent that policies that promote greater freedom of economic activity are promoted, national economies will benefit more from remittances.
Keywords: Remittances; institutions; economic growth; GMM; EU